(untitled) - Lane, Robert E. (New York, 1972)
In this sense, thay are humanist, but of course thay employ the concepts and methodss of the social sciences. The political effects of two major social changes, the growth of affluence and of scientific knowledge.
Keywords: Political psychology,Political sociology,Tâm lý học chính trị,Xã hội học chính trị